ANALISIS SISTEM KEAMANAN JARINGAN MENGGUNAKAN SWITCH PORT SECURITY PADA WARNET GRAMIT KELURAHAN SASA - Ishak, Nursalima; Hamza, Sahriar; Hamid, Mustamin (Program Studi Pendidikan Teknologi Informasi, 2023)
Along with the development of technology, the need for computer networks and the internet will be increasingly important, both in the fields of education, employment and other fields. The goal to be achieved in this research is to analyze and develop a network security system using switch port security at gramit cafe, Sasa Ternate Selatan village. The results of the research carried out by the author at the gramit cafe are that by carrying out port testing on PC servers, clients and CCTV connected and connected properly after the ping test is carried out, this is reinforced by information from each image that the ping status is successful with 0% packet loss .